Identifikasi Faktor Kegagalan Hasil Produksi Busa dengan Sistem Pakar Metode Dempster Shafer dan Certainty Factor - Dhyana Lowrenza (Jurnal Informatika Ekonomi Bisnis, 2022)
Foam is a derivative product made from PPG (Propylene Glycol) or Polyether Polyol which is then mixed with additives and catalysts. So it will produce foam that is used in the springbed and mattress industry. The foam is produced first by using a mixer machine. After the mixer, dispensing will be carried out (pouring the material into the mold) then the foam will be blown off and the foam production process is complete. Failure to produce foam often results in losses in terms of raw materials, costs, and time. To avoid the failure of the same foam production, a research was carried out by designing an expert system application that aims to be able to identify the factors causing the failure of foam production and to reduce the risk of failure of foam production. The data needed in this study were obtained from PT Bungo Permai Lestari. The data is then processed using the Dempster Shafer method and the Certainty Factor method. The results of this study are to provide output in the form of certainty values ​​from failure of foam production, factors causing failure of foam production, as well as solutions to failure of foam production obtained through consultation using the Dempster Shafer method and the Certainty Factor method by selecting symptoms that match the results. foam production. So this research can help PT Bungo Permai Lestari to find out the causes and solutions to the failure of foam production and can reduce the risk of failure during foam production.